Microbially produced vitamin B12 contributes to the lipid-lowering effect of silymarin - Sun, Wen-Long; Hua, Sha; Li, Xin-Yu; Shen, Liang; Wu, Hao; Ji, Hong-Fang (Nature communications, 2023)
Silymarin has been used for improving hepatic damage and lipid disorders, but its action mechanism remains to be clarified. Here, we investigate the contributions of the gut microbiota to the improvement of liver lipid metabolism by silymarin. We find i) strong and significant microbial shifts upon silymarin but not silibinin treatment; ii) over 60% variations of liver fat are explained by silymarin-induced bacterial B12 production in male rats but not in male germ-free mice; iii) fecal microbiota transplantation confirms their protective roles against liver fat accumulation; iv) upregulation of one-carbon metabolism and fatty acid degradation pathways are observed based on the liver transcriptome analyses; and v) in humans the delta changes of serum B12 associate negatively with the fluctuations of serum triglycerides. Overall, we reveal a mechanism of action underpinning the lipid-lowering effect of silymarin via the gut microbiota and its vitamin B12 producing capabilities. Silymarin has been used for improving hepatic damage and lipid disorders, but its action mechanism remains to be clarified. Here, the authors reveal a mechanism of action underpinning the lipid-lowering effect of silymarin via the gut microbiota and its vitamin B12 producing capabilities.